The story of Doctor Dolittle - Lofting, Hugh, 1886-1947. (New York : Tor, 1998)
The adventures of a kind-hearted doctor, who is fond of animals and understands their language, as he travels to Africa with some of his favorite pets to cure the monkeys of a terrible sickness.
"A Tom Doherty Associates book.".
5.0
3-6
Keywords: Animals -- Fiction; Fantasy; Animals -- Fiction; Fantastic fiction